Weak-light single-pixel imaging based on self-powered photodiodes - An, Ran; Xiong, Simiao; Wu, Hao; Mai, Wenjie; Ji, Zhong; Liu, Yujin; Xia, Chengqi; Li, Yaping (Laser physics letters, 2025)
In recent years, single-pixel imaging, especially Fourier single-pixel imaging (FSI) has received increasing attention, and weak-light single-pixel imaging is an important subject worth studying. A high-quality CCD-based digital camera can typically obtain an image by collecting around 10 5 photons per pixel. However, how does this compare in single-pixel imaging, and how can it be improved? We built a high-precision FSI system to study the weak-light problem. Using this system, we obtained clear images under weak light conditions of 400 pW cm −2 and concluded that the minimum number of photons required for imaging in this system is approximately 10 5 per pixel per projection. We then analyzed in detail the noise problem which determines the minimum imageable light intensity, and proposed methods to improve the minimum. Furthermore, we demonstrated two possible applications, non-line-of-sight imaging and underwater imaging. This work may promote more extensive applications of single-pixel imaging in daily life and scientific research.